A Comparative Study on the Interaction Performance of the Striped Flea Beetle with Different Fungal Entomopathogens - Xinhua Pu; Xiangyu Hu; Ke Zhang; Alexander Berestetskiy; Vsevolod Dubovik; Qiongbo Hu; Qunfang Weng (Agriculture)
The striped flea beetle (SFB), Phyllotreta striolata, is a significant pest of cruciferous crops. Entomopathogenic fungi (EPF) hold great promise for the integrated pest management (IPM) of the SFB. However, the lack of understanding of the different interactions between the SFB and EPF restricts the development of mycoinsecticides. This study aims to elucidate the interaction performance of the SFB with three EPF—Beauveria bassiana BbPs01 (Bb), Metarhizium robertsii MrCb01 (Mr), and Cordyceps javanica IjH6102 (Cj). The bioassay results indicated that the virulences of EPF to the SFB adults were recorded as Bb > Mr > Cj. Then, the EPF with distinct infection pathways were observed, in which Bb penetrated the SFB cuticle via germ-tubes and appressoria, Mr typically invaded using appressoria, while Cj employed germ-tubes. Moreover, the SFB with different symptoms following infection by the EPF species were recorded. Bb primarily caused SFB adults to lose their appetite, become sluggish, and die rapidly. In contrast, SFB adults infected with Mr often experienced shivering, uncoordinated movement, and slower death. Cj-infected larvae frequently displayed dendrite-like melanization originating from the spiracles, while infected adults exhibited weak shivering and slow death, which seems similar to Mr. Our findings provide novel insights into the interactions between EPF and insects and offer valuable materials for enhancing the application of mycoinsecticides in the control of the SFB.